THE USE OF ARTISTIC DEVICES IN SOBIR SAYQALI'S "RAVZAT USH-SHUHADO" (Intent Research Scientific Journal, 2025)
The article analyzes the use of artistic devices and means of expression in Sobir Sayqali's "Ravzat ush-shuhado," a work that artistically depicts events from Islamic history. The author reveals the distinctive features of using artistic devices through generalized conclusions.